Staphylococcus aureus and methicillin-resistant Staphylococcus aureus in workers at a university hospital: colonization and beliefs in health. - Elaine Drehmer de Almeida Cruz; Elucir Gir (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
The carrier state of methicillin-resistant Staphylococcus aureus is pointed as infection predictor among hospitalized patients, and factor for environmental and person to person dissemination, including health service workers, when colonized are commonly associate to outbreaks1. Prevention of professional colonization risk is associated to behavior and dependent of knowledge and beliefs in health. Objective: analyze the prevalence of Staphylococcus aureus in saliva of workers of the nursing, medical, physiotherapist, occupational therapist and cleaning teams, at a big university hospital. Method: epidemiologic longitudinal study carried out with 486 workers between April 2006 and June 2008, three saliva samples were collected and a data collection instrument with open and closed questions was applied. Staphylococcus aureus were isolated from the clinical specimen and characterized by phenotypes; the methicillin-resistant were submitted to mecA gene detection and SCCmec chromosome cassette identification. Quantitative data from the instrument and the laboratory results were organized and processed with EPI-Info software and analyzed by descriptive statistics. Data from the open questions were submitted to quantitative discourse analysis and analyzed according to the categories which emerged from the answer subjects. The ethics principles in research were observed. Results: among the researched workers, 60,9% were colonized by Staphylococcus aureus in saliva, of those 67,9% were transitory carriers and 32,1% persistent carriers; the prevalence of meticillin-resistant Staphylococcus aureus among the isolated was 15,7%. The average prevalence of methicillin-resistant Staphylococcus aureus was 12,7% and higher among nurses' aides (21,4%) and cleaning aides (20,6%) and lower among nurses (4,5%) and doctors (5,9%). The mecA gene was detected in 36,9% of the methicillin-resistant Staphylococcus aureus. The most valorized preventive measures were the use of individual protective devices and adoption of basic hygiene and isolation measures. Workers understand their susceptibility to colonization and see it as dependent of their health conditions. The consequences of colonization and the benefits of adopting preventive attitudes were associated to the patient, family and workers themselves; knowledge and working conditions were referred to as the main interventions in adopting control and prevention measures. Conclusions: workers presented high prevalence of Staphylococcus aureus in saliva, indicating mouth as an important body site to investigate colonization by methicillin-resistant Staphylococcus aureus and potential source to its dissemination2. The phenotypic profile revealed differences on the antimicrobial sensibility profile between isolated resistant and meticillin-resistant; as well as the multi-resistance of the methicillin-resistant Staphylococcus aureus to the other antimicrobials tested. The study of workers' knowledge and beliefs allowed a better comprehension of the professional behavior and contributed to the planning of educational actions3;4, targeting methicillin-resistant Staphylococcus aureus prevention and control.